High expression of post-treatment Ki-67 status is a risk factor for locoregional recurrence following breast-conserving surgery after neoadjuvant chemotherapy. Issue 5 (May 2015) - Yamazaki, N.; Wada, N.; Yamauchi, C.; Yoneyama, K.
Abstract Introduction During the past decade, neoadjuvant chemotherapy (NAC) has been increasingly used in patients to reduce large tumors to a size eligible for breast-conserving therapy (BCT). However, the association between NAC and Ki-67 has not yet been fully elucidated. The aim of this study was to evaluate the prognostic significance of Ki-67, specifically after NAC followed by BCT, particularly in terms of locoregional recurrence (LRR). Methods A total 217 patients who received BCT after NAC were retrospectively analyzed. In these patients, immunohistochemistry analyses defined four tumor subtypes, Luminal A, Luminal B, Triple negative, and HER2 type. Ki-67 was examined by immunohistochemistry in both pretreatment core needle samples and post-treatment surgical excision specimens. High Ki-67 expression was defined as >20%. The prognostic factors LRR, locoregional relapse-free survival (LRRFS), and overall survival (OS) were analyzed. Results In total, LRR developed in 14 patients, and the 5 year-LRRFS was 94.2%. Post-treatment high Ki-67 expression, triple negative, the presence of lymphovascular invasion, and histological grade 3 were significantly high in LRR for prognostic factors (P < 0.05). There were significant differences in Kaplan–Meier method for LRRFS curves according to these three factors for patients receiving BCT following NAC (P < 0.05). There was a significant difference in the 5 year-OS for patients with and without LRR (41.7% vs. 93.9%, P < 0.001). Conclusion Post-treatment high Ki-67 expression could be one of the important prognostic factors of LRR, and require careful follow-up on LRR at the time of surveillance.